Compartment boundaries and the control of Drosophila limb pattern by hedgehog protein. - Basler, K.; Struhl, G. (Nature, 1994)
Drosophila limbs are subdivided into anterior and posterior compartments which derive from adjacent cell populations founded early in development. Evidence is now provided that posterior cells organize growth and cell patterning in both compartments by secreting hedgehog protein and that hedgehog protein acts indirectly by inducing neighbouring anterior cells to secrete decapentaplegic or wingless protein.